Adverse reaction after transfusion of Red Blood Cells in a patient aged 97 years - case report - Paulina Marta Kasperska-Dębowska; Eliza Oleksy; Anna Wojtczak; Małgorzata Nowicka (Kazimierz Wielki University, 2021)
During hospitalization 97 years old patient had blood transfusion. This procedure lead to overload of cardiovascular system. Pharmacotherapy gradually improved the general condition of the patient. The patient was discharged in a stable state. Doubts arise; when blood should be transfused, in which cases should a blood transfusion be discontinued, what should be the recommendation for a blood transfusion for older people over the age of 90. There is a need for further research in geriatrics regarding the transfusion of blood and its components.